AN ALTERNATIVE CONSTRUCTION OF THE MOUFANG LOOP M(G, 2) - Andrew Rajah (Proceedings of ICMSA, 2006)
In [3], Orin Chein defined and constructed a class of Moufang loops called the M(G, 2) with a product rule which is rather complicated. We provide an alternative definition ofM(G, 2) with a much simpler product rule.